Trichoderma Compost Making Technology in the Bumi Sari Farmers Group of Bongkasa Village, Abiansemal District, Badung Regency, Bali Province - Andriani, A. A. S. P. R.; Ni Ketut Sri Rukmini; I Ketut Sunadra; Modesta Sriayuningsi Todo; Maria Scolastika Dede (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Bumi Sari Farmers Group is located in Abiansemal Village, Badung. This group of 10 members manages chilli plantations. The problem faced by the Bumi Sari Farmers group is that chili plants often experience symptoms of permanent wilting, and fruit rot attacked by pathogenic fungi. Trichoderma compost is a solution to overcome this problem. With the concept of controlling plant pest organisms (OPT) naturally, to get healthy plant cultivation and be free from diseases. In this activity, the farmer group has been able to make Trichoderma compost and has applied it to chilli plants. From the survey results, the damage to chilli flowers reached 75%. Furthermore, after the application of Trichoderma compost fertilizer treatment, it suppressed diseases in chilli plants by 46.4%. From this activity, it was able to reduce yield loss by 25% and increase farmers' income by 20%.